Limited formal education is strongly associated with lower cognitive status, functional disability and frailty status in older adults - Brigola,Allan Gustavo (2019)
ABSTRACT. Limited formal education is still common in ageing populations. Although limited formal education seems to be independently and negatively associated with cognition, functional abilities and frailty in ageing, no studies have examined whether the gradient of limited formal education has an impact on health in later life. Objective: to examine the relationship of limited formal education with cognitive status, functional abilities, and frailty status. Methods: a cross-sectional study was conducted involving 540 older adults stratified into groups: no formal education, 12-24 months of education, and 25-48 months of education. Cognitive screening (MMSE), functional abilities (Lawton Index), and frailty (CHS criteria) were measured. Regression analyses were performed. Results: 27% had no formal education, 21% had 12-24 months of formal education, and 55% had 25-48 months of formal education. Limited formal education has a clear gradient of negative impact: No formal education was associated with scoring below MMSE cut-off scores (OR = 7.9), being totally/partially dependent for IADLs (OR = 2.5) and frail (OR = 2.0). Having 12-24 months of education was associated with scoring below MMSE cut-off scores (OR = 5.2) and with being frail (OR = 2.0). The No formal education group was 10.1 times more likely to have worse cognitive scores, worse functional abilities and frailty/pre-frailty status concomitantly (CCoFF), while older adults who had 12-24 months of education had a 4.6 times greater chance of having CCoFF. Conclusion: limited education had a gradient association with cognitive performance, functional disability and frailty. These findings clearly emphasize the importance of prevention through education from childhood to older age.